Partnerships for community building and governance in master planned communities: a study of Vasity Lakes at Gold Coast. - Bajracharya, B.; Earl, G.; Khan, Shahed (University of Florida/ University of Illinois at Chicago, 2008)
The development and management of master planned communities (MPCs) involveachieving the twin goals of building a sense of community and creating a distinctiveplace identity. The roles of private, public and community sectors in realising thesegoals of MPCs have been evolving over time with the increasing role of developers inprovision of services with the local government playing a regulatory/facilitative role andcommunity calling for greater engagement and local control.The major objective of the paper is to critically examine the nature and outcomes ofcollaboration between developers, local/state governments and existing/emergingcommunity groups in the development of new MPCs in South East Queensland,Australia. The paper will review emerging theories of community building and placemaking to develop an analytical framework for collaboration of stakeholders for MPCs inSouth East Queensland. The paper will conduct a case study of an emerging masterplanned community of Varsity Lakes (343 hectares with expected population of 7,800 in2010) in Gold Coast and examine the contributions of the public-private-communitypartnerships in: 1) developing a strong sense of community; and 2) creating a distinctiveand vibrant place. The paper will also briefly discuss the historic evolution of masterplanned communities in South East Queensland and the changing role of public-privatecommunitypartnerships to provide the context for detailed study of Varsity Lakes.As part of research methodology, the study will carry out: 1) content analysis of developer's brochures and government documents; 2) visual analysis of place makingelements in MPC; and 3) key informant interviews with developer, local governmentdepartment as well as community groups. The paper will use the case study to drawlessons for effective governance of master planned communities for greater communityengagement and stronger sense of place identity.